Formação contínua: o fortalecimento da dupla gestora na Educação Infantil - Szabo, Kelly (2021)
The present research aimed to understand what evidences the impact in the work of Kindergarten administration pairs, consisting of Pedagogical Coordinator and Principal, through continuous training. We focused on continuous training to qualify school management actions for improving the quality of education. Through correlated research, we observed it is valid to investigate and theorize it, considering the important findings on conceptions of Kindergarten, in-service training, and managerial attributions. Such findings, however, did not reveal whether continuous training indeed impacts on strengthening the administration pair’s actions, or if such partnership builds up to improving the quality of educational processes developed at Kindergarten Schools (CEI), specifically those partnered to the public educational system. For such investigation, 10 Principals and 10 Pedagogical Coordinators, who worked together at partnered CEIs and attended the Infancies in Focus Project (Projeto Infâncias em Foco) at DRE Itaquera, were invited as participants. We used questionnaires (LAVILLE; DIONE, 1999), semi-structured interviews (BOGDAN; BIKLEN, 2010); (SZYMANSKY, 2011) and yarning circles (WARSCHAUER, 2017a; 2017b; 2017c), as instruments and strategies for producing data. For data analysis, we used NVivo 12 software and adopted content analysis, inspired by Bardin (2011). Results showed that Principals and Pedagogical Coordinators seek to open space for collaboration between peers, aiming at keeping good relationships and at developing school as a whole, which runs through the assurance of continuous training as public policy for their development. We were able to see the articulation between different sectors as a way to reinforce their process management, in an attempt to reduce the work overload of both Principals and Pedagogical Coordinators, making it possible to focus on their core tasks: leading pedagogical actions to promote quality education for babies and toddlers. We identified the participants’ continuous search for establishing good relationships – personally, professionally, and with the community – through dialog and partnership, what was seen as key features by most Principals and Pedagogical Coordinators. Participants also revealed that continuous training for all workers ensures quality of education in Early childhood